PRIORITAS PENGEMBANGAN PRODUK PENUNJANG PERTANIAN PERKOTAAN (STUDI KASUS: TOMPEYAN, YOGYAKARTA) - Christmastuti Nur; Stefani Natalia Sabatini (Narada : Jurnal Desain dan Seni, 2022)
The increasing rate of population growth and urbanization resulted in a shift in the function of agricultural land into residential areas which r has an impact on the occurrence of a food crisis due to population growth that is not balanced with the rate of food production. One of the efforts to grow food self-sufficiency in urban areas, especially on narrow land, is to practice urban agriculture. This study aims to determine the priority for the development of products that support the productivity of urban farming practices with the case study in the city of Yogyakarta. Data was collected through a survey with a sample of 25 households in RW 3 Tompeyan, Tegalrejo District, Yogyakarta City, who practice urban farming. Data were analyzed quantitatively distributively to find a trend of significance. The results of the study show that products that support plant watering, development of planting containers, and products that facilitate the application of waste in urban agriculture are top priorities that designers and manufacturers of agricultural equipment must develop to support urban farming practices in the City of Yogyakarta, as well as in other regions in Indonesia. with similar characteristics.